Profiling GC-MS Ethanol Extract of Putri Malu Leaves (Mimosa pudica L.) and Its Potential as Anti Cholesterol In Vitro - Adhityasmara, Dhimas; Indriyanti, Erwin; Ramonah, Dewi; Elisa, Novi (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
Cholesterol plays a crucial role in cell building and hormone production in the body, but excessive levels can lead to various diseases. Elevated cholesterol levels increase the risk of cardiovascular diseases such as atherosclerosis. Natural remedies for high cholesterol treatment are commonly sourced from medicinal plants containing many phytochemicals. One such plant is the Putri Malu (Mimosa pudica L.) leaf. This study aims to evaluate the chemical composition of Putri Malu leaf extract and its potential anti-cholesterol effects in vitro. The extraction process used in this study was maceration, followed by GC-MS profiling analysis and the Liebermann Burchad method with UV-Vis spectrophotometry. The findings of this study revealed the presence of five chemical constituents in the extract. Among them, the second and fourth peaks had the highest abundance of acacetin at 14.08% and diosmetin at 73.79%, respectively. The ethanol extract of Putri Malu leaves demonstrated strong anti-cholesterol activity in vitro with an IC50 value of 24.8993, indicating its potential as an agent for treating hypercholesterolemia. Further research is required to evaluate this extract's efficacy in vivo and investigate its underlying mechanism of action.